2013
DOI: 10.1186/1471-2407-13-565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lifestyle and single nucleotide polymorphisms on breast cancer risk: a case–control study in Japanese women

Abstract: BackgroundLifestyle factors, including food and nutrition, physical activity, body composition and reproductive factors, and single nucleotide polymorphisms (SNPs) are associated with breast cancer risk, but few studies of these factors have been performed in the Japanese population. Thus, the goals of this study were to validate the association between reported SNPs and breast cancer risk in the Japanese population and to evaluate the effects of SNP genotypes and lifestyle factors on breast cancer risk.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 31 publications
5
48
0
Order By: Relevance
“…The frequency of allele A in this study is 42.8% in the total sample set and 37.69% in control group, supported the data of previous studies in the Asian population, which was about 34.8 -39.3% Han et al, 2011). Specifically, in this study, 37.69% allele A in the control group was in the same range as the reported 34% in Caucasian descendants, 37.8% in Chinese (Hap Map-HCB) and 30.0% in Japanese (Hap Map -JTP) (Mizoo et al, 2013). Distribution of this allele in Vietnamese which is the same as its distribution in other populations in Asia can be understood as they are in the same geography distribution and may share the same genetic distribution.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The frequency of allele A in this study is 42.8% in the total sample set and 37.69% in control group, supported the data of previous studies in the Asian population, which was about 34.8 -39.3% Han et al, 2011). Specifically, in this study, 37.69% allele A in the control group was in the same range as the reported 34% in Caucasian descendants, 37.8% in Chinese (Hap Map-HCB) and 30.0% in Japanese (Hap Map -JTP) (Mizoo et al, 2013). Distribution of this allele in Vietnamese which is the same as its distribution in other populations in Asia can be understood as they are in the same geography distribution and may share the same genetic distribution.…”
Section: Discussionsupporting
confidence: 91%
“…This polymorphism was significantly associated with the risk of breast cancer in different Asian populations, including Chinese with strong association [ORs (95% CI) = 1.35 (1.17 -1.57), p = 4.1×10-5 for allelic analysis and [P for trend = 1.54×10−30] (Lin et al, 2014). In Japanese women, the allele A has been strongly associated with breast cancer with [ORs (95% CI) = 1.37 (1.11 -1.70), p = 0.05] (Mizoo et al, 2013) or [ORs (95% CI) = 1.31 (1.13 -1.52) and 1.37 (1.06 -1.76) for the AG and AA genotypes, p for trend = 2.51×10−4] (Cai et al, 2011). SNP rs2046210 had a population attributable risk of 18.9% plus an estimated 2.1% excess familial risk of breast cancer (Zheng et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…When stratified by ethnicity, this significance was lost in those of African descent, but it was maintained in European and Asian populations. Mizoo et al (2013) performed a case-control study that associated rs2046210 with higher BC risk in Japanese women. Our results also suggest that rs2046210 T allele carriers (TC and TT genotypes) have a significantly elevated BC risk compared with those with CC genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another GWAS of 1600 Icelandic BC patients and 11,563 controls, followed by a replication study of 4554 affected individuals and 17,577 control subjects, showed the rs3803662 C>T TNRC9 variant to be associated with increased ER-positive BC risk (Stacey et al, 2007). However, in a Japanese study, the rs3803662 T allele exhibited no connection with risk of BC (Mizoo et al, 2013). As conflicting results have been obtained, the clinical importance of this polymorphic gene is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 18 studies involving 44,820 cases and 58,316 controls met the inclusion criteria and were used in pooled analyses (Antoniou et al, 2008;Garcia-Closas et al, 2008;Li et al, 2009;Mcinerney et al, 2009;Gorodnova et al, 2010;Latif et al, 2010;Liang et al, 2010;Tamimi et al, 2010;Campa et al, 2011;Han et al, 2011;Slattery et al, 2011;Harlid et al, 2012;Shan et al, 2012;Mizoo et al, 2013;Ottini et al, 2013;Chen et al, 2014;Elematore et al, 2014). The primary features of these investigations are shown in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%